PENERAPAN MODEL PEMBELAJARAN EVERYONE IS A TEACHER HERE TERHADAP MINAT DAN HASIL BELAJAR SISWA PADA KONSEP PENCEMARAN LINGKUNGAN DI KELAS VII MTs Al-Ikhlas KAIRATU - Amaludin, La; Awal, Rawia (Program Studi Pendidikan Biologi FKIP Unpatti, 2022)
Background: Everyone Is A Teacher Here Everyone Is A Teacher Here learning model is that everyonecan become a teacher. This model is very appropriate to get class participation as a whole or individually.This model provides an opportunity for each student to act as a teacher for his friends. With this learningmodel, students who have not wanted to be involved will participate in learning effectively.Methods: This research was conducted in class MTs Al-Ikhlas. The study used descriptive analysis whichwas used to determine the students' cognitive, affective and psychomotor learning outcomes.Results: The results showed that the mastery of students' biology concepts before the application of thelearning model Everyone is a teacher here is said to be very low. This can be seen from the average scoreobtained by students in the initial test, which is 42% of the KKM KD specified, which is 70 which is includedin the failed qualification. After the application of learning the formative test results obtained by the studentsbecame better with the average percentage of achievement on the formative test of 90%.Conclusion: Based on the results of research and discussion, it can be concluded that the application ofthe Everyone Is a Teacher Here learning model can improve student learning outcomes on the concept ofEnvironmental Pollution. This is evidenced by the Final Score that is sufficient for the KKM.